Impact of Male Hormonal Contraception on Prostate Androgens and Androgen Action in Healthy Men: A Randomized, Controlled Trial - Mostaghel, Elahe A. (Endocrine Society, 2012)
CONTEXT: Male hormonal contraception (MHC) combines hypothalamic-pituitary-gonadal axis blockade with exogenous androgen delivery to maintain extragonadal androgen end-organ effects. Concern exists that MHC may adversely impact prostate health. OBJECTIVE: The objective of the study was to determine the molecular impact of MHC on intraprostatic androgen concentrations and androgen action. DESIGN: This was a single-blind, randomized, placebo-controlled study. SETTING: The study was conducted at an academic medical center. PARTICIPANTS: 32 healthy men aged 25–55 yr participated in the study. INTERVENTION: Interventions included placebo, daily transdermal testosterone (T) (T-gel), T-gel + depomedroxyprogesterone acetate (T+DMPA), or T-gel + dutasteride daily (T+D) for 12 wk, and prostate biopsy during treatment wk 10. MAIN OUTCOME MEASURES: Serum and prostate androgen concentrations and prostate epithelial-cell gene expression were measured. RESULTS: Thirty men completed the study. Serum T levels were significantly increased in T-gel and T+D groups compared with baseline (P < 0.05) but were decreased with the addition of DMPA. Intraprostatic androgens were no different from placebo with T-gel treatment. Addition of DMPA to T resulted in 40% lower intraprostatic dihydrotestosterone (DHT) concentration (P = 0.0273 vs. placebo), whereas combining dutasteride with T resulted in a 90% decrease in intraprostatic DHT (P = 0.0012), 11-fold increased intraprostatic T (P = 0.0011), and 7-fold increased intraprostatic androstenedione (P = 0.0011). Significant differences in global or androgen-regulated prostate epithelial-cell gene expression were not observed. Androgen-regulated gene expression correlated with epithelial-cell androgen receptor and prostatic DHT in placebo, T-gel, and T+DMPA arms and with T and androstenedione levels in the T+D arm. CONCLUSIONS: MHC regimens do not markedly alter gene expression in benign prostate epithelium, suggesting they may not alter risk of prostate disease. Longer-term studies examining the impact of MHC on prostate health are needed.